2023
DOI: 10.3390/life13010165
|View full text |Cite
|
Sign up to set email alerts
|

Human Heart Morphogenesis: A New Vision Based on In Vivo Labeling and Cell Tracking

Abstract: Despite the extensive information available on the different genetic, epigenetic, and molecular features of cardiogenesis, the origin of congenital heart defects remains unknown. Most genetic and molecular studies have been conducted outside the context of the progressive anatomical and histological changes in the embryonic heart, which is one of the reasons for the limited knowledge of the origins of congenital heart diseases. We integrated the findings of descriptive studies on human embryos and experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The embryonic development process begins with the formation of the heart, which is regulated by a group of cardiac core transcription factors. This important process is tightly controlled to ensure the proper development of this vital organ ( 40 ). Numerous previous studies have demonstrated that Nkx2.5 is regulated at the transcriptional level by many transcription factors and cis-regulatory elements upstream of the Nkx2.5.…”
Section: Transcription Regulation Of Nkx25mentioning
confidence: 99%
“…The embryonic development process begins with the formation of the heart, which is regulated by a group of cardiac core transcription factors. This important process is tightly controlled to ensure the proper development of this vital organ ( 40 ). Numerous previous studies have demonstrated that Nkx2.5 is regulated at the transcriptional level by many transcription factors and cis-regulatory elements upstream of the Nkx2.5.…”
Section: Transcription Regulation Of Nkx25mentioning
confidence: 99%
“…Structurally, the heart tube contains an outer layer composed of cardiomyocytes and an inner layer comprising endothelial cells; it also has an anteriorly positioned atrial pole (outflow) and a posterior venous pole (inflow). After attaining its shape at E8.5, the linear heart tube undergoes a rightward looping process driven by uneven growth and remodeling, resulting from the recruitment of cardiac cells differentiated from progenitor cells in the SHF [10]. This event leads to the formation of primitive atria and ventricles.…”
Section: Introductionmentioning
confidence: 99%
“…The development process of the large vessel system lasts from the third to the eighth week of gestation. [4]. Bae et al [5] proposed two distinct models of embryogenesis that can explain this system's forms.…”
Section: Introductionmentioning
confidence: 99%